Diversity of Marine Fungi as a Source of Bioactive Natural Products - Li, Dehai (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Bioactive metabolites from marine-derived fungi are known to be an important source of drug discoveries. Natural product scientists have explored various environments, such as the deep ocean and polar regions, as well as marine mangrove ecosystems, to discover unique fungi strains which could produce new bioactive structures. The aim of this Special Issue is to highlight the diversity of fungi derived from different marine environments, as well as their potential as producers of bioactive marine natural products. Innovative scientific results, as well as approaches and methodologies applied in marine natural product discovery areas, are encouraged. Studies on the biosynthesis and bioactivities of marine natural products are also welcome. For this Special Issue, we invited academic and industry scientists to submit reviews and original and conceptual research articles highlighting diversified marine fungi as a source of bioactive natural products.